Awareness to Clinical Antimicrobial Sensitivity Reporting: a questionnaire-based study. - Akhtar, Anees; Sultan, Asfia; Khan, Fatima; Khan, Shariq Wadood; Tayyaba, Uzma; Bhattacharya, Bhaswati (International Journal of Human and Health Sciences (IJHHS), 2023)
Antimicrobial resistance (AMR) has emerged as one of the leading public health threats of the 21st century. The clinical microbiology reporting of culture and antimicrobial susceptibility test, if communicated and understood correctly, may lead to effective treatment without increasing the AMR burden. This questionnaire-based study was conducted to access the awareness of microbiology reporting and resistance related comments among clinicians. A questionnaire consisting of 10 questions was prepared and circulated among clinicians of different departments to assess the level of awareness to microbiology reporting maintaining their confidentiality, and their responses were recorded manually. 62 (91%) out of 69 clinicians were aware of the remarks written on the microbiology report, and 35 (51%) clinicians were agreed that these remarks were relevant to guide them for antimicrobial prescriptions. When asked about remarks like “MRSA and High content gentamycin and streptomycin sensitivity interpretation”, 34(50%) and 24(35%) responded correctly, respectively. On asking about their action to remarks like “Contaminated” and “Commensal flora”, 51(73%) clinicians provided the right answer. Some direct questions related to avoidance of particular antibiotics as for example use of Tigecycline in Bacteremia and Nitrofurantoin (intrinsic resistance) in cases of proteus spp. 20 (29%) and 42(62%) participants were aware of the standard guidelines respectively, while 29(42%) clinicians responded correctly that in case of ventilator associated pneumonia (VAP), intermediate sensitivity colistin should be given inhalationally. There is an urgent need for the microbiology laboratory to incorporate various comments, advices and additional messages. Also, there should be a clear communication and case based discussion between clinician and microbiologist. International Journal of Human and Health Sciences Supplementary Issue 02: 2023 Page: S130-S137